Correction to: 33rd Annual Meeting & Pre-Conference Programs of the Society for Immunotherapy of Cancer (SITC 2018). Issue 1 (13th February 2019) - Berry, Sneha; Giraldo, Nicolas; Nguyen, Peter; Green, Benjamin; Xu, Haiying; Ogurtsova, Aleksandra; Soni, Abha; Succaria, Farah; Wang, Daphne; Roberts, Charles; Stein, Julie; Engle, Elizabeth; et al.
Abstract : After publication of this supplement [1, 2], it was brought to our attention that due to an error authors were missing in the following abstracts. This has now been included in this correction.